2020
DOI: 10.3390/cells9061550
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Supplementation during the In Vitro Maturation of Oocytes Improves the Developmental Competence of Preimplantation Embryos: Potential Link to SIRT1/AKT Signaling

Abstract: Nicotinamide (NAM), the amide form of vitamin B3, plays pivotal roles in regulating various cellular processes including energy production and maintenance of genomic stability. The current study aimed at deciphering the effect of NAM, when administered during in vitro maturation (IVM), on the developmental competence of bovine preimplantation embryos. Our results showed that low NAM concentrations reduced the oxidative stress and improved mitochondrial profile, total cleavage and 8–16 cell stage embryo develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…The antioxidant activity of melatonin during the process of embryonic development has been comprehensively studied, whereas the impact of high NAM concentrations on such developmental process has been fewly reported [6,7,13,18,38]. To date, the potential linkage between melatonin and NAM in the context of embryo development has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The antioxidant activity of melatonin during the process of embryonic development has been comprehensively studied, whereas the impact of high NAM concentrations on such developmental process has been fewly reported [6,7,13,18,38]. To date, the potential linkage between melatonin and NAM in the context of embryo development has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte Maturation and Actin Stabilization. We have previously reported that high NAM concentrations can negatively affect the process of embryo development [13]. To investigate whether melatonin can alleviate this effect, bovine oocytes were treated with 20 mM NAM for 22 h in the presence and absence of 10 −7 M melatonin.…”
Section: Melatonin Reduces Nam-associated Impairment Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The COCs were collected and cultured, as previously mentioned [ 50 ]. Briefly, COCs, aspirated from ovarian follicles using 18-gauge needles connected to 50 mL tubes containing TL-HEPES, were washed, and those comprising more than three cumulus layers were collected under a stereomicroscope (Olympus SZ51, Tokyo, Japan), washed three times in TL-HEPES, and cultured (around 50 COCs per well) in four-well plates containing 700 μL IVM medium (TCM-199 supplemented with 10% ( v/v ) fetal bovine serum (FBS), 10 μg/mL follicle-stimulating hormone (FSH), 1 μg/mL estradiol-17β, 0.2 mM sodium pyruvate, 10 ng/mL epidermal growth factor (EGF), 0.6 mM cysteine, 0.1 mg/mL streptomycin, and 100 IU/mL penicillin), in the absence or the presence of juglone (12.5, 25.0, and 50.0 μM) at 38.5 °C and 5% CO 2 for 22 h. Checking the literature for juglone in vitro studies revealed that it could be used at concentrations in the range of 1.0–100.0 µM [ 25 , 30 ].…”
Section: Methodsmentioning
confidence: 99%